MENTAL IMAGERY AND SELF-CONFIDENCE AND THEIR RELATIONSHIP TO THE SKILL PERFORMANCE LEVEL OF RESERVE PLAYERS OF AL-RAMADI CLUB AND AL-FAHAD FOOTBALL CLUB - Waad Mohammed Attallah; Luay Ali Attallah (Proximus Journal Publishing, 2026)
The study aimed to identify the degree of mental imagery and self-confidence and their relationship to the skill performance level of the reserve players of Al-Ramadi Club and Al-Fahad Football Club. The research sample consisted of reserve players from Al-Ramadi Club and Al-Fahad Football Club, totaling (80) players. (10) players were excluded for the pilot study, bringing the total sample size to (70) players. Each club was divided separately, resulting in (35) players for each club. The researchers used the descriptive method with a correlational approach due to its suitability for the nature of the research. The researchers concluded that the lack of financial and moral support, as well as the unavailability of stadiums in some clubs, may negatively affect the players' performance.
Keywords: Mental Imagery; Self-Confidence; Their Relationship